Cost-effectiveness study of the MitraClip system for mitral regurgitation treatment in inoperable patients - E. G. Fedina; K. A. Perova; T. S. Teptsova; D. S. Shchurov (Евразийский Кардиологический Журнал, 2021)
The study aims to estimate the MitraClip system’s cost-effectiveness compared with optimal medical therapy in adult patients with inoperable mitral regurgitation and assess its impact on the budget of the Russian Federation health system.Materials and methods. The cost-effectiveness analysis of the MitraClip system was carried out using the Markov model. The time horizon was three & five years. The budget impact analysis (BIA) model compared the costs of treating patients distributed across different management practices. Standard management practice included only optimal medical therapy. Expected management practice included different patient allocation between the MitraClip system and optimal medical therapy. The time horizon for the budget impact analysis was five years. Results. The incremental cost-effectiveness ratio (ICER) per additional quality-adjusted life-year (QALY) gained of the MitraClip system in comparison with optimal medical therapy was 6,271,657 rubles in three years and 3,451,342 rubles in five years. Based on the BIA results of the MitraClip system, its use would lead to an increase in costs by 12.6 billion rubles (+6.09%, minimal scenario), by 37.8 billion rubles (+18.28%, optimal scenario) or by 63 billion rubles (+30.47%, maximum scenario).Conclusion. As a result of the analysis performed, it was found that economic efficiency is noted with an increasing time horizon of up to five years. The obtained ICER values are comparable with the average values obtained in other foreign cost-effectiveness studies. The use of this technology will lead to an increase in direct medical costs by 6.09% over five years compared to the current management practice. In more comprehensive MitraClip system implementation (maximum scenario), direct medical costs will increase by 30.47% compared to the current management practice.